2013
DOI: 10.1165/rcmb.2012-0337oc
|View full text |Cite
|
Sign up to set email alerts
|

Functional Genomic Assessment of Phosgene-Induced Acute Lung Injury in Mice

Abstract: In this study, a genetically diverse panel of 43 mouse strains was exposed to phosgene and genome-wide association mapping performed using a high-density single nucleotide polymorphism (SNP) assembly. Transcriptomic analysis was also used to improve the genetic resolution in the identification of genetic determinants of phosgene-induced acute lung injury (ALI). We prioritized the identified genes based on whether the encoded protein was previously associated with lung injury or contained a nonsynonymous SNP wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 120 publications
(127 reference statements)
0
10
0
Order By: Relevance
“…Digoxin is a cardiovascular medicine that increases the free calcium concentration by inhibiting the sodium/potassium-transporter ATPase subunit alpha-1 (ATP1A1) [30]. ATP1A1 has been associated with lung injury in mice [31], and its expression was significantly changed in cultured cells infected with H5N1 in this study. Our results indicate that H5N1-induced ALI in mice might be reduced by the ATP1A1 inhibitor digoxin.…”
Section: Plos Pathogensmentioning
confidence: 60%
“…Digoxin is a cardiovascular medicine that increases the free calcium concentration by inhibiting the sodium/potassium-transporter ATPase subunit alpha-1 (ATP1A1) [30]. ATP1A1 has been associated with lung injury in mice [31], and its expression was significantly changed in cultured cells infected with H5N1 in this study. Our results indicate that H5N1-induced ALI in mice might be reduced by the ATP1A1 inhibitor digoxin.…”
Section: Plos Pathogensmentioning
confidence: 60%
“…This supports the conclusion that the increased tissue damage observed in DSS-treated Mbd4 −/− mice is not due to an overactive innate immune response by the Mbd4 −/− immune system; instead, it suggests that the Mbd4 −/− colonic epithelium itself is more susceptible to inflammation-induced injury than WT colonic epithelium. Interestingly, a recent study in mice identified two non-synonymous polymorphisms in functional domains of Mbd4 that are associated with significant differences in survival after phosgene-induced acute lung injury, supporting the idea that Mbd4 status of epithelial cells may be important for their response to chemical insult [ 69 ].…”
Section: Discussionmentioning
confidence: 89%
“…ZFAND4 promotes cell proliferation by activation of cyclin-dependent kinase and downregulation of p21 and p53 in SGC-7901 cells, which are derived from human gastric cancer 13. In addition, transcriptional upregulation of ZFAND4 is also observed in phosgene-induced acute lung injury in mice 17. However, there is still a lot of uncertainty surrounding the functional roles of ZFAND4 in human malignancies because the literature concerning ZFAND4 is limited.…”
Section: Discussionmentioning
confidence: 99%